Implikatur Dalam Komentar Warganet Terhadap Nasib Honorer Guru Yang Dirumahkan: Studi Kasus Di Tik Tok - Dina Tazkiyah; Ayu Puspita Indah Sari (Universitas Muhammadiyah Surabaya, 2026)
The issue of eliminating the status of honorary workers, particularly teachers, is currently a hot topic on social media, including TikTok. Many netizens have responded in the comments section, often containing implicit meanings reflecting dissatisfaction, hope, and criticism. The purpose of this study is to determine the types and functions of implicatures that appear in netizen comments. Using a qualitative descriptive method, data were collected from screenshots collected from Bahri Permana's TikTok account discussing the issue of honorary workers. The findings revealed two types of implicatures: conversational implicatures and conventional implicatures. There are three functions of implicatures: directive, assertive, and expressive.